Enhancing the contrast of the grey-scale image based on meta-heuristic optimization algorithm; Soft Computing; Vol. 26, iss. 13 - Ali H. Kh. Hussain Khan; Shameem A. Ahmed; Suman K. Kumar; Seyedali M. Mirjalili; Oliva Navarro D. A. Diego Alberto; Ram S. Sarkar (2022, 2022)
Title screen